Research perspectives in vehicle routing and scheduling - Bott, Kevin; Ballou, Ronald H. (Transportation research. Part A: general, 1986)
The problem of vehicle routing and scheduling has been a popular research subject, yet much of the research has focused on developing methods that are accurate and computationally efficient but that are generally of limited scope. This article classifies these methodologies and appraises each class. Perhaps more important, the article identifies those restrictions and extensions that should be incorporated into a generalized vehicle routing and scheduling methodology and, therefore, points the direction for future research.